“The Bravo Boys” Band versus Mozart: the Issue of Cultural Message in Contemporary German Language Textbooks - Głowińska, Beata (Respectus Philologicus, 2020)
Wolfgang Amadeus Mozart had to give way to The Bravo Boys music band. This is what the authors of the textbook entitled Ping Pong 1 and Ping Pong neu 2 have decided to do in the current edition of their book. So, they decided to replace its contents concerning the Composer himself and other representatives of classical music with the report from the concert of the BB. The article attempts to determine who, what characters from the real world populate in contemporary German textbooks, what cultural content it has and whether or not it conforms with the core curriculum standards of the Polish education system. To this end, selected German language textbooks have been analyzed along with the practice material offered by them. The authors of examined textbooks have almost completely abandoned depicting representatives of high culture, of German culture. They have been replaced with representatives of mass culture: mainly models, actors, athletes as well as politicians. Their common feature is the fact that they are universally known: the majority are celebrities while some of them are scandalists. The fact that these persons can be easily recognized seems to increase the students’ learning involvement, but it cannot constitute the only criterion of such selection. The article stresses the responsibility of textbook authors for the quality of cultural message addressed to children and teenagers.